Cannabis and psychopathology: 2024 Snapshot of a meandering journey - Tathagata Mahintamani; Diptadhi Mukherjee; Debasish Basu (Indian Journal of Psychiatry)
Background: Cannabis has been associated with psychopathology since ancient times, but controversies continue despite important advances in the field. This article is the fourth one in our decadal series of review articles that have been providing an update snapshot of the meandering journey of the research findings in this area. Aims: This narrative review of a comprehensive literature search over the past 10 years aims to provide an update and current understanding, while raising unanswered questions for the future, focusing on the following areas: (a) nosological changes in cannabis-related psychiatric syndromes; (b) psychopathology associated with the newer category of synthetic cannabinoids; (c) cannabis withdrawal syndrome); (d) cannabis and psychosis; (e) cannabis and mood disorders; (f) cannabis and suicidality; (g) prenatal cannabis use and psychopathology in the offspring; (h) effect of recent liberal policy overhaul on cannabis control in certain countries/areas on psychopathology and adverse outcomes; (i) cannabis and cognition; and (j) cannabis, psychopathology, and genetics. Methods: The data search strategies involved a combination of electronic databases and manual hand-searching of relevant publications and cross-references using selected search terms. The primary electronic search focused on Medline and PubMed Central databases but extended to databases such as Google Scholar, PsychINFO, Scopus, and Ovid for specific sections. Key references identified through electronic and manual searches provided additional material. Inclusion criteria for the review spanned studies published between January 2014 and June 2024, with more emphasis placed on recent studies (post-2020) while ensuring historical coverage. Results: The narrative review aimed to be comprehensive, including a broad range of research without strict methodological exclusions. Strengths and limitations of cited research are discussed when applicable, maintaining consistency with three prior reviews. We focused on psychopathology and psychiatric syndromes, human (rather than animal) studies, and applied (rather than basic) research. We have only focused on policy with reference to psychopathology and not on that entire area because that would be beyond the scope of this article. There are important updates in all the areas covered. There are newer syndromal entities in ICD-11, which also includes synthetic cannabinoids for the first time. Cannabis withdrawal syndrome has been better characterized. The association between cannabis and psychosis has been robustly established especially for very high-potency cannabis and for vulnerable populations, particularly young people. Work is in progress elucidating the causal mechanisms. The links between cannabis and mood disorders as well as suicidality and cognitive impairment are better characterized, though questions remain. Recent liberalizing policies on cannabis have produced newer findings on prenatal and accidental cannabis use (with deleterious effects on the offspring) and on later psychopathology (mixed findings, but a documented increase in emergency visits related to recent cannabis use). This is an area which will require active monitoring for new data. Conclusion: The field of cannabis use and psychopathology continues to collect new data and settle some old controversies while raising new questions, which are important to address in view of the wide use of cannabis worldwide and its implications for public health.